Використання інформаційних систем і технологій в управлінні тваринництвом - Мороз, Світлана Іванівна; Moroz, Svitlana (Дніпровський державний аграрно-економічний університет, 2020)
В умовах поширення глобальних мереж та постійного розширення спектру і функціональності інформаційних продуктів, актуальним є дослідження інформаційних систем і технологій, спеціалізованих програмних продуктів, спрямованих на розв’язання завдань управління тваринництвом та визначення перспектив їх використання фахівцями сільськогосподарських підприємств, фермерами та домогосподарствами. Проаналізовано вітчизняні та іноземні програмні продукти для автоматизації задач сектору тваринництва (Master : Тваринництво, Акцент: Племінний облік у свинарстві, Управління сільськогосподарським підприємством для України, DelPro, DairyComp 305, Uniform Software, рішення CONTO). Рішення про їх впровадження приймаються керівництвом централізовано. Використання експертних систем та мобільних додатків є більш персоналізованим й вони призначені для кращого виконання фахових обов’язків. Перспективними для працівників тваринницького сектору є: довідкові, розрахункові, дистанційного доступу, геолокаційні, комунікаційні мобільні сервіси і додатки. Цільовою аудиторією мобільних додатків також є фермерські господарства та домогосподарства, яким фінансово не вигідно придбання повноцінних систем. Global digitalization trends include the widespread introduction of information systems and technologies in the management of information flows and production processes of the livestock sector of agricultural enterprises, the transfer of commercial relations to a virtual environment, the use of network resources and specialized portable devices and mobile applications. Given the rapid growth of networks and the constant expansion of the range of information products and their functionality, the aim of the article is to study information systems and technologies, specialized software products aimed at solving problems of animal husbandry management and identifying prospects for their use. It is established that promising areas of use of information systems and technologies in animal husbandry are information support, application of information systems and technologies in management of production processes, accounting, purchasing and sales activities, optimization of resource use, decision support. Ukrainian and foreign software solutions for automation of tasks in the livestock sector are analyzed (Master: animal husbandry, Accent: Pedigree accounting in pig farming, Agricultural Enterprise Management for Ukraine, DelPro, DairyComp 305, Uniform Software, CONTO solutions, Coral programs). It is established that the introduction of accounting systems and management systems of production processes requires significant financial investments and changes in the organizational structure of management. Therefore, the decision on their centralized use is made by the top management of the enterprise. Due to the need to integrate different types of systems, the use of cloud solutions for management systems in holdings is not appropriate. Farms with small volumes of data transfer operations to the clouds will save money on system maintenance. Decisions on the use of expert systems and mobile applications are made personally, mostly at the specialist level, to expand his automated workplace in order to better perform his duties. Several main groups of mobile applications useful for animal husbandry workers have been identified: help, calculators, remote access, geolocation, communication services. The target audience of mobile applications is also farming and households, which are not financially profitable to purchase full-fledged systems.
Using of information systems and technologies in management of animal husbandry
Keywords: інформаційні системи; information systems; інформаційні технології; information technologies; програмні засоби; software; мережі; networks; тваринництво; animal husbandry